The Family Check-Up 4 Health (FCU4Health): Applying Implementation Science Frameworks to the Process of Adapting an Evidence-Based Parenting Program for Prevention of Pediatric Obesity and Excess Weight Gain in Primary Care - Smith, Justin D.; Berkel, Cady; Rudo-Stern, Jenna; Montaño, Zorash; St. George, Sara M.; Prado, Guillermo; Mauricio, Anne M.; Chiapa, Amanda; Bruening, Meg M.; Dishion, Thomas J. (Frontiers in Public Health, 2018)
Implementation experts have recently argued for a process of “scaling out” evidence-based interventions, programs, and practices (EBPs) to improve reach to new populations and new service delivery systems. A process of planned adaptation is typically required to integrate EBPs into new service delivery systems and address the needs of targeted populations while simultaneously maintaining fidelity to core components. This process-oriented paper describes the application of an implementation science framework and coding system to the adaptation of the Family Check-Up (FCU),for a new clinical target and service delivery system—prevention of obesity and excess weight game in primary care. The original FCU has demonstrated both short- and long-term effects on obesity with underserved families across a wide age range. The advantage of adapting such a program is the existing empirical evidence that the intervention improves the primary mediator of effects on the new target outcome. We offer a guide for determining the levels of evidence to undertake the adaptation of an existing EBP for a new clinical target. In this paper, adaptation included shifting the frame of the intervention from one of risk reduction to health promotion; adding health-specific assessments in the areas of nutrition, physical activity, sleep, and media parenting behaviors; family interaction tasks related to goals for health and health behaviors; and coordinating with community resources for physical health. We discuss the multi-year process of adaptation that began by engaging the FCU developer, community stakeholders, and families, which was then followed by a pilot feasibility study, and continues in an ongoing randomized effectiveness-implementation hybrid trial. The adapted program is called the Family Check-Up 4 Health (FCU4Health). We apply a comprehensive coding system for the adaptation of EBPs to our process and also provide a side-by-side comparison of behavior change techniques for obesity prevention and management used in the original FCU and in the FCU4Health. These provide a rigorous means of classification as well as a common language that can be used when adapting other EBPs for context, content, population, or clinical target. Limitations of such an approach to adaptation and future directions of this work are discussed.